THE END OF THE XIX - BEGINNING OF THE XX CENTURY THE STATE OF ENTREPRENEURSHIP IN TURKESTAN: FROM THE MMETROPOLIS TO THE MONOPOLY - Fayzulla S. Tolipov, (International Scientific and Current Research Conferences, 2022)
The article describes the establishment of the first business enterprises in Turkestan in the late XIX - early XX centuries, their activities and the liquidation of entrepreneurship after the establishment of Soviet power, the transition from a metropolis to a monopoly. It also discusses the sources of profit of private enterprises and their liquidation during the years of Soviet rule.